The New Cold War: Religious Nationalism Confronts the Secular State By Mark Juergensmeyer. Berkeley: The University of California Press, 1993, 202 pp. (American Journal of Islam and Society, 1994)
The collapse of the Soviet Union, which resulted in the demise of thefonner bipolar system in international relations, has led writers to offerpredictions about the future framework of international political relationships.Francis Fukuyama posits the end of history as a result of the endof the cold war. Samuel Hlllltington speculates that the post-cold warworld will be divided according to differences in civilizations: a "clashof civilizations." Unlike Hwttington, Mark Juergensmeyer argues that anyfuture conflict will have a religious nature. Hwttington predicts that thestruggle will occur on the international level, whereas Juergensmeyer saysit will take place on the nation-state level, for religious nationalism willchallenge the dominant secular ideology that now rules nation-states.Before proceeding, two important elements asserted by Juergensmeyershould be kept in mind: the conflict between secular nationalismand religious nationalism will take place in the Third World and will beconfined to the borders of the nation-state. In other words, Islamic movementswill not be united and their concern will be limited to their respectivecmmtries. Based on these assertions, we can assume that the WestwiH remain secular and unthreatened by religious revolts, and that theconflict may develop from the national to the international level (i.e.,between western secular states and nonwestem nation-states dominatedby religious groups).The book is based on interviews conducted by the author withleaders of various religious groups and an analysis of their writings. Muslim,Hindu, Buddhist, Sikh, and Jewish movements are studied. In thefirst chapter, "The Loss of Faith in Secular Nationalism," the authorexamines the emergence of nationalism in the Third World through theworks of Hans Kohn and Donald Smith. The main theme here is the religiousrejection of secular nationalism. He asserts that secular nationalistsare perceived by religious nationalists as partners in a western-led globalconspiracy against religion:An example occurred in 1991 during the Gulf War: Islamic politicalgroups in Egypt reversed their initial condemnation of Iraq'sinvasion of Kuwait when the United States sent thousands of ...